Hubungan Motivasi Belajar Dengan Hasil Belajar Mahasiswa Tahun Masuk 2013 Jurusan KTP FIP UNP Pada Mata Kuliah Komputer Grafis - Meldi Ade Kurnia Yusri (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2014)
This research was motivated by the low student learning outcome at Curriculum and Technology of Education in Education of Sciences Faculty, State University of Padang. The purpose of this research was to reveal the relationship of learning motivation with learning outcome of student TM 2013 semester 2 in KTP FIP UNP majors. This research used quantitative methods to the type of correlational research. The sample in this research were 77 students TM 2013 semester 2 in KTP FIP UNP majors, used Slovin formula with proportional random sampling technique. The research instrument was structured in the form of a questionnaire with Likert scale models, after being tested looking for validity and reliability. The data were analyzed using simple linear regression. The results showed that there was a significant positive relationship between learning motivation and learning outcome of students TM 2013 semester 2 majoring in Curriculum and Educational of Technology at 0.492. Based on the findings of this study concluded that the independent variables, namely learning motivation played a very important in improving learning outcome, in addition to other variables.